Pengaruh Latar Belakang Pendidikan dan Pengalaman Kerja Terhadap Etos Kerja Karyawan BSI KCP. Panyabungan: Nursaibah Tanjung - Nursaibah Tanjung (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2026)
This study aims to determine the influence of educational background and work experience on the work ethic of BSI KCP Panyabungan employees. This study was conducted at BSI KCP Panyabungan. The research method used is a quantitative research method. The population of this study were BSI KCP Panyabungan employees. Using the sampling method with saturated samples or total sampling, the sample used was 14 respondents. The Independent Variables in this study are Educational Background (X1), and Work Experience (X2), while the dependent variable in this study is Work Ethic (Y). The data used are primary data obtained from respondents' answers through the questionnaire given. The tool used in this study is SPSS version 21. The results of this study are based on the results of SPSS calculations that educational background partially has a positive and significant effect on the work ethic of BSI KCP Panyabungan employees, with a t-count value (3,501)> t-table (2,201) with a significance value of 0.000 <0.05. These results indicate that Ha is accepted and H0 is rejected. Work Experience partially has a positive and significant effect on the work ethic of BSI KCP Panyabungan employees, with a t-count value (6,344)> t-table (2,201) with a significance value of 0.000 <0.05. So that makes the hypothesis in this study Ho rejected Ha accepted. Simultaneously educational background and work experience have a positive and significant effect on the work ethic of BSI KCP Panyabungan employees, with a calculated F value = 163,520> F table = 3.98 with a significance of 0.000 <0.05 so that makes the hypothesis in this study Ho rejected Ha accepted. Keywords: Educational Background, Work Experience, Work Ethic